The Management of Small-Scale Industries by Women Entrepreneurs - A Study With Reference to Virudhunagar District - Mathivannan, S.; Selvakumar, M. (Prabandhan: Indian Journal of Management, 2009)
The entire change and development of civilization to a large extent is the result of trade, commerce and industrialization. In this development, the human resource in general and entrepreneur in particular play a pivotal role. In India, from the very beginning, women have been managers of the kitchen and have solely dominated the area of household activities. The hidden entrepreneurial potential of women has gradually been changing with the growing sensitivity to the role and economic status in society. Today, women entrepreneurs represent a group of women who have broken away from the beaten track and are exploring new avenues of economic participation. Woman entrepreneur is regarded as a person who accepts a challenging role to quench her personality needs and to become economically independent by making suitable adjustment in both family and social life. Among the reasons for women to run organized enterprises are their skill and knowledge, their talents and abilities in business and a compelling desire of wanting to do something positive. The increase in women's education, industrialization, urbanization, social and occupational mobility, the emergence of nuclear families, westernization, politico-social movements and changes in the value system have made the educated women take to certain careers.